Comportamento defensivo, prejuízo na memória e ativação diferencial do hipocampo dorsal e ventral em camundongos machos submetidos ao protocolo de derrota social - Costa, Vinicius Fresca da (Universidade Federal de São Carlos, 2021)
The hippocampus (HPC) is a brain area well known to regulate memory and spatial navigation but also known to be a very plastic brain structure that is influenced by other areas like the medial prefrontal cortex (mPFC) as well as by stress-related stimuli. In the present study, we investigated the effects of the exposition of chronic social defeat stress (SDS) in male mice on (i) the avoidance behavior assessed in the social interaction test (SIT); (ii) the anxiety-like behavior in the elevated plus-maze (EPM); (iii) the working memory in the object recognition test (ORT); (iv) The presence of projections from the left mPFC to the dorsal HPC and ventral HPC (dHPC and vHPC) was also investigated (v) ΔFosB, CaMKII as well as ΔFosB+CaMKII labeling in neurons located in the dorsal and ventral hippocampus (d & vHPC). Results showed that chronic SDS induced defensive- and anxiety-like behaviors and memory impairment, followed by decrease and increase in ΔFosB labeling in the dHPC and vHPC, respectively. In the vHPC, an increase in the CaMKII labeling was also shown. There was a presence of projections from the left mPFC to both dHPC and vHPC. Together, these findings suggest that chronic exposure of mice to SDS may have (a) overactivated glutamatergic neurons in the vHPC, leading to an increase in defensive- and anxiogenic-like responses, and (b) inhibited the dHPC, causing memory impairment. Given that chronic SDS also impairs the left mPFC functioning, these SDS-induced effects on behavior and vHPC & dHPC may be related to a failure of the left mPFC control on the neuronal activity of the hippocampus.
Defensive behavior, memory impairment and dorsal and ventral hippocampus's differential activation on socially defeated male mice
Keywords: Ansiedade; Hipocampo; Córtex Pré-Frontal medial; Camundongo; Estresse de derrota social; Evitação social; Prejuízo na memória; Neurotransmissão glutamatérgica; Neuroanatomia; Neurotracejamento; Anxiety; Hippocampus; Medial Prefrontal Cortex; Mice; Chronic Social Defeat Stress; Social avoidance; Memory impairment; Glutamatergic neurotransmission; Neuroanatomy; Neuronal tracing; CIENCIAS BIOLOGICAS::FARMACOLOGIA::NEUROPSICOFARMACOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::NEUROFISIOLOGIA